Parameters optimization to minimize the vibrations E ects during the milling process - Ribeiro, J.E. (2017)
In nowadays the increasing productivity in the shortest possible time and with high quality is undoubtedly one of the biggest challenges for the industry. Recently, the industry has turned to CNC machines very often, since they work automatically and are able to achieve high precision with a high performance. In this sense, the vibration has been presented during the last decades as one of the main limiting factors for the improvement of productivity specially in machining operations. This work contributes to the reduction of vibrations, proposing the use of optimization methods to minimize vibrations using milling parameters (cutting speed,feed speed, axial penetration and radial penetration) related to the section area. This study presents a theoretical analysis on the materials and tools used throughout the experimental trials, as well as the methods and programs used. During this study, two optimization methods were used: the Taguchi method and the Response Surfaces method.